Macrophages participate in local and systemic inflammation induced by amorphous silica nanoparticles through intratracheal instillation - Yang M (Dove Medical Press, 2016)
Man Yang,1,2 Li Jing,1,2 Ji Wang,1,2 Yang Yu,1,2 Lige Cao,1,2 Lianshuang Zhang,1,2 Xianqing Zhou,1,2 Zhiwei Sun1,2 1School of Public Health, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Environmental Toxicology, Capital Medical University, Beijing, People’s Republic of China Abstract: Silica nanoparticles (SiNPs) are amongst the most commonly used materials in the field of nanomedicine and, therefore, their influence on organisms has drawn increasing attention in recent years. Most reports have focused on the single tissue reactions induced by SiNPs. Herein, the reaction of primary organs to SiNPs following intratracheal instillation in mice was analyzed by histopathology and ultrastructure observation. Following elucidation of the role of macrophages in local and systemic inflammation, the underlying mechanisms were explored using a macrophage cell line in vitro. The results suggest that macrophages swallow the SiNPs and secrete inflammatory factors by activating the NLRP3 inflammasome, thus participating in local and systemic inflammation. Keywords: silica nanoparticles, inflammation, macrophages, organs, NLRP3 inflammasome